THE STAKEHOLDERS’ PERCEPTIONS ABOUT THE FINANCIAL EDUCATION PROCESS IN A SCHOLAR DYNAMIC - Sayed, Samir (Revista Ibero-Americana de Humanidades, Ciências e Educação, 2026)
In the Brazilian formal education system, projects for implementing financial education have formally existed since 2010 and are increasingly by the following years. This paper’s objective is to analyze with agents involved in the elementary educational system, their understanding about financial education and how the formalization is being done, which strategies are being used and what are the points for improvement. The data was collected through five interviews with women involved in some way in the educational environment of children in an elementary school dynamic. We perceived that the interviewees have some awareness about the nuances of financial education, even though in their respective school phases, some of them claim not to have had access to this theme. Regarding financial education in formal education, it was possible to verify that in some schools the theme is being treated with teaching strategies, not only in mathematics, but also bringing the theme across other subjects. However, it was clear that even after the official introduction in the Common National Curricular Base, as of 2020, there is a lack of training for educators to apply the techniques with children. As a matter of the pandemic context, 2020 was atypical and this may have been a strong cause for the education systems in general not undergoing major changes. The interviewees, when asked about the perspectives of the Brazilian scenario in personal finance, understand that the future is promising and that the teachings currently given in school to children since kindergarten will generate good results in the medium and long term, reflecting even in the average indebtedness levels of Brazilians and changing some consumption habits.